Wireless Technology to Handle Marketing Risks - Sayed Ahmed, Ebtehal Atta Elsayed; Abdullah, Ibrahim; Noor Azlinna, Azizan (2015)
Wireless market is the selling and buying of goods or services over the Internet, Therefore E-commerce is a modern business methodology that addresses the needs of organizations, merchants, and consumers to cut costs while improving the quality of goods and services and increasing the speed of service delivery. The technology, the business models, and the value chain relationships are new and in many ways different from traditional business environments. The uncertainty concerns the character and degree of those differences. In this paper we will address these risks and address based on three points: first, types of risks which are presented in e-commerce. Second, similarities and differences between e-commerce risks and the risks in other business environments. Finally, methodologies that can be used to control these risks. The proposed framework provides an overview of what is happening in the wireless domain to provide marketers, managers and market researchers with a realistic view of using and predicting the wireless technology market. The proposed methodology can develop a security and risk management policy, which identifies and analyses risks, and the potential impact that they will have on the operations.